2018
DOI: 10.2337/db18-602-p
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Hyperglycemia Causes Vascular Hypoperfusion at Optic Nerve Head in Diabetic Patients (DM)

Abstract: Background: OCT angiography (OCTA) and laser speckle flowgraphy (LSFG) are novel and noninvasive imaging modalities which could evaluate fundus blood flow quantitatively. However, the role of OCTA and LSFG as diagnostic tools has not been widely investigated. Previous reports indicated that NO, reduced by hyperglycemia, exerts a key role for the autoregulation of retinal blood flow. We designed this study to evaluate the retinal blood flow by OCTA and LSFG in hyperglycemic DM. Method: 10 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Experimentally, a high FPG level itself exhibits a short-term protective effect during optic nerve stress [37]. However, decreased vessel density in the optic nerve head of hyperglycemic patients has been reported clinically [38]. In accordance with this, we also found that the incidence of T2D was increased with the baseline FPG level in subjects without T2DM, showing 1.2% of incidence in subjects with FPG < 80 mg/dl and 7.1% of incidence in those with FPG between 100 mg/dL and 126 mg/dL (S1 File).…”
Section: Plos Onementioning
confidence: 99%
“…Experimentally, a high FPG level itself exhibits a short-term protective effect during optic nerve stress [37]. However, decreased vessel density in the optic nerve head of hyperglycemic patients has been reported clinically [38]. In accordance with this, we also found that the incidence of T2D was increased with the baseline FPG level in subjects without T2DM, showing 1.2% of incidence in subjects with FPG < 80 mg/dl and 7.1% of incidence in those with FPG between 100 mg/dL and 126 mg/dL (S1 File).…”
Section: Plos Onementioning
confidence: 99%
“…Se han observado también defectos a nivel de la capa de fibras retiniana, uno de los hallazgos característicos de los pacientes con glaucoma, en sujetos con DM [267], [268]. Siguiendo en esta línea, se ha descrito una disminución de la densidad vascular a nivel de la cabeza del nervio óptico en pacientes con niveles elevados de glucosa plasmáticos [269].…”
Section: Ingesta De Carbohidratosunclassified